Perbandingan Klasifikasi Data Calon Pendonor Darah dengan Algoritma K-Nearest Neighbor dan Support Vector Machine - RACHMAT RAMADHAN (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Blood plays an important role in the human body. Meeting the need for blood is very important to improve the quality of health services and save a person's life. According to World Health Organization guidelines, blood from a donor cannot be used after 42 days. The national blood reserve that meets the standards of the International Health Organization (WHO) is 2% of the population. To know and understand the behavior of blood donors, it is very important to increase blood supply in the future, one of which is by using an algorithm to predict the behavior of blood donors. To classify prospective blood donors using the K-Nearest Neighbors Algorithm and Support Vector Machine. The data used comes from the PMI UTD, South Jakarta City, the primary data collection for blood donors. The test is done by comparing the training data and testing data. The results of the test show that the Support Vector Machine produces an accuracy of 90% greater than the K-Nearest Neighbors Algorithm which only has an accuracy of 76% with a data comparison of 60:40 with a dataset of 200 data. .